Environmental laboratory exercises for instrumental analysis and environmental chemistry - Dunnivant, Frank M., ....- (Hoboken : Wiley, 2004)
This complete summary of laboratory work presents a richly detailed set of classroom-tested experiments along with background information, safety and hazard notes, a list of chemicals and solutions needed, data collection sheets, and blank pages for compiling results and findings. This useful resource also: Focuses on environmental, i.e., "dirty" samples Stresses critical concepts like analysis techniques and documentation Includes water, air, and sediment experiments Includes an interactive software package for pollutant fate and transport modeling exercises Functions as a student portfolio of documentation abilities Offers instructors actual samples of student work for troubleshooting, notes on each procedure, and procedures for solutions preparation.
Keywords: Instrumentele analyse; Laboratoriumtechnieken; Milieuchemie